Converging Development of English as Foreign Language Listening and Reading Comprehension Skills in German Upper Secondary Schools - Spoden, Christian; Fleischer, Jens; Leucht, Michael (Frontiers in Psychology, 2020)
Receptive skills in English as a second language are important for students on the verge of entering higher education as this student group (aged 17–19) is expected to apply English regularly in their later life. Previous research in this age group in Germany already implied an increasing overlap between both skills in this age group, although robustness of this effect across student groups with different learning experiences was not tested. We used language assessment data collected from upper secondary schools (i.e., from 17–19-year-old students) in Germany to compare correlations at the beginning and the end of upper secondary education in groups of students from (1) language-related versus nonlanguage-related study profiles and (2) from students with frequent versus less frequent self-reported English-language out-of-school learning activities. In all of these groups, correlations were increasing, indicating converging skills in upper secondary education. The results are discussed in terms of implications for current theories of language research.